Predicting commercial fishing vessel disasters through a novel application of the theory of man-made disasters. (December 2020) - Case, Samantha L.; Lucas, Devin L.
Highlights: Vessel disasters are a leading contributor to work-related deaths in the commercial fishing industry. The role of prior vessel casualties in vessel disasters was explored based on the theory of man-made disasters. A history of vessel casualties was identified as a predictor of vessel disasters. Safety management systems and industry-level guidance are needed to reduce risks and failures in vessel systems. Abstract: Introduction: Vessel disasters (e.g., sinkings, capsizings) are a leading contributor to fatalities in the U.S. commercial fishing industry. Primary prevention strategies are needed to reduce the occurrence of vessel disasters, which can only be done by developing an understanding of their causes and risk factors. If less serious vessel casualties (e.g., loss of propulsion, fire, flooding) are predictors of future disasters, then reducing vessel casualties should in turn reduce vessel disasters and the accompanying loss of life. Method: This case-control study examined the association between vessel casualties and disasters using fishing vessels in Alaska during 2010–2015. Results: The findings show that vessels that experienced casualties within a preceding 10-year period were at increased odds of disaster. Other significant predictors included safety decal status and hull material. Practical Applications: The results of this analysis emphasize the importance of implementing vessel-specific preventive maintenance plans. At an industry level, specific prevention policies should be developed focusing on high-risk fleets to identify and correct a wide range of safety deficits before they have catastrophic and fatal consequences.